HAM DALAM PERSPEKTIF ILMU-ILMU SYARI'AH - Muhammad Adil (Pusat Studi Gender dan Anak Universitas Islam Negeri Raden fatah palembang, 2014)
The tragedy of twin tower, World Trade Center (WTC) New York last September 11th 2001, has brought a lot of global problems. They are namely the issues of ideology differences and aggression to some countries, which are assumed having connection with what is called high class terrorism net, al Qaeda and having special relation with Osama bin Laden. Although without approval from United Nation Organization (UNO), USA and his allies strike a drum of war to fight against world terrorism movements. By using Ilmu Syari'ah perspective, the writer in this article studies about basic human rights in relation with the act of attacking other countries.ملخص: وكانت مأساة سطوط قصر التؤمان المركز التجارى الدنيا نيويورك, الا مريكية المتحدة فىالتاريخ 11 من سفتمبر 2001 السبق, تترك المسائل العولمية الطثير, من امر اختلاف الايديولوجية الى هجوم البلاد التى تظن ان لها اتصال وثيق بالشيئ الدى يسمى بالشبك الارهابى الكبير